(untitled) (mathematica didactica, 2021)
This paper reports on a research project about using interactive worksheets designed based on typical student difficulties concerning functional thinking. The dynamic materials focus on the representational transfer between iconic situational and graphical representation and were integrated in an intervention with a 7th grade Austrian secondary school class to foster functional thinking. Several types of data were collected through diagnostic tests, diagnostic interviews, and observations during the intervention. The qualitative study particularly pays attention to the intuitive conceptions of students and whether and in what ways interactive worksheets may influence students’ conceptions. In this paper, a general overview of the research project as well as some key findings are presented.